Is Problematic Exercise Really Problematic? A Dimensional Approach - Chamberlain, Samuel R. (CNS Spectr, 2020)
OBJECTIVE: Though moderate exercise has numerous health benefits, some individuals may become excessively pre-occupied with exercise, endorsing features akin to ‘addiction’. The aim of this study was to evaluate the relationships between Problematic Exercise (viewed dimensionally), quality of life, and psychological measures. METHODS: Young adults were recruited from an established population-based cohort in the United Kingdom, and completed an online survey. The factor structure of the Exercise Addiction Inventory (EAI) was characterized. Relationships between dimensional EAI factor scores and other variables (impulsivity, compulsivity, emotional dysregulation) were elicited. RESULTS: 642 individuals took part in the study (mean age 23.4 years, 64.7% female). The EAI yielded two factors – a ‘general factor’, and a ‘relationship conflict factor’. Both EAI factor scores were associated with disordered eating, impulsivity (UPPS), and compulsivity (CHIT). Only the relationship conflict factor score was significantly associated with impaired quality of life (all domains), and with maladaptive personality traits (emotional dysregulation and obsessive-compulsive personality disorder traits). Few participants met conventional threshold for full exercise addiction (1.1%). CONCLUSION: Higher Problematic Exercise scores, in a sample largely free from Exercise Addiction, were associated with impulsive and compulsive personality features, emotional dysregulation, and disordered eating. Further research is needed to examine whether these results generalize to other populations (such as gym attendees), and are evident using more rigorous in-person clinical assessment rather than online assessment. Longitudinal research is needed to examine both positive and negative impacts of exercise, since moderate exercise may in fact be useful for those with impulsive/compulsive tendencies, by dampening negative emotional states or substituting for other more damaging types of repetitive habit.